62. SURVEY OF CARDIOVASCULAR DISEASE PREVALENCE IN THE ELDERLY AT THONG NHAT HOSPITAL FROM 2017 TO 2022 (Vietnam Journal of Community Medicine, 2024)
Background: Currently, the global population of elderly individuals is rapidly increasing, including in Vietnam. Cardiovascular disease is a scientific term encompassing not only heart diseases (coronary artery disease, valvular heart disease, cardiomyopathies, and congenital heart conditions) but also hypertension and diseases related to cerebral vessels, carotid arteries, and peripheral circulation. Vietnam's disease model reflects that of a developing country, with infectious diseases and malnutrition still prevalent, although these are gradually declining. Non-communicable diseases, such as cardiovascular diseases, cancer, congenital and genetic disorders, metabolic conditions, and obesity, are on the rise. Therefore, this study was conducted to investigate the prevalence of cardiovascular disease among the elderly in Vietnam.Methods: Cross-sectional descriptive study using retrospective investigation from 01/2017 – 12/2022: All medical records of patients ≥60 years old hospitalized at the Cardiovascular Center - Thong Nhat Hospital.Results: The study was conducted on 25,315 elderly patients, with a mean age of 63.34 ± 16.50 over the 6 years. The average age of inpatients showed a gradual increase over the years. The four most common cardiovascular conditions over the six years were hypertension (57.95%), ischemic heart disease (43.33%), arrhythmias (26.12%), and heart failure (10.91%). Infective endocarditis was the least common, at 0.09%. The prevalence of cardiovascular diseases increased with age, while the average length of hospital stay for all cardiovascular conditions tended to decrease over the years. The number of hospital admissions for common cardiovascular conditions decreased over the years, while admissions for less common diseases tended to increase.Conclusions: The elderly population has a high rate of morbidity and hospitalization for cardiovascular diseases, which significantly impacts their quality of life. The concerning effects on patients' lives warrant attention and require targeted interventions.
Keywords: Cardiovascular disease; the elderly